Aloísio Magalhães, cartemando - Braga, Isis Fernandes (Centro de Letras e Artes, 2020)
Aloísio Magalhães creativity is known in both cultural as artistic fields. In this articleI try to approach the oeuvre he created according to the remarks made duringthe printing of the Cruzeiro bills he had designed and which he followed up in Holland.Back to Brazil, Aloísio used the procedure of the form repetition on commonpost-cards, thus creating the Brazilian series and a series derived from the postcards of the collection Chefs d’Oeuvre de la Photographie, from the AgatheGaillard Gallery, Paris.The Cartemas, as they were named by Antonio Houaiss, where exhibitedthroughout the world, and became a reference to Aloísio’s work.These collections attracted me and, in this research, I elected one of theCartemas to essay a structural investigation.In order to do this, I believe it is necessary to understand Aloísio Magalhãestrajectory and his connections with graphic design in Brazil